Advanced control techniques for a direct matrix converter - Vijayagopal, Manjusha (2017)
Model Predictive Control (MPC) has gained popularity in the recent years for control of power converters. One of the drawbacks of this control method is the variable switching frequency operation. By obtaining a fixed switching frequency operation while maintaining the advantages of MPC, the performance of these controllers can be enhanced. This thesis investigates the implementation of two novel control methods to control a direct matrix converter. The proposed control methods combine the features of classical MPC and the Space Vector Modulation technique to develop a hybrid predictive controller with an inbuilt modulation scheme. The resulting methods are known as Modulated Model Predictive Control (M2PC) and Direct Predictive Current-error Vector Control (DPCVC). The M2PC maintains all the characteristics of MPC (such as fast transient response, multi-objective control using only a single feedback loop, easy inclusion of non-linearities and constraints of the system, the flexibility to include other system requirements within the controller) adding the advantages of operating at a fixed switching frequency and improving the quality of the controlled waveforms. Simulation and experimental results employing the control method to a direct matrix converter feeding an RL load and an induction motor drive are presented. The DPCVC results in fixed switching frequency operation and improved current quality compared to M2PC, owing to the advanced modulation technique it utilises to generate the desired voltage vectors. It also inherits features such as fast transient response and multi-objective control without cascaded loops from the MPC. This method is implemented to control the load currents of a direct matrix converter feeding an RL load and an induction machine and the simulation and experimental results depicting the same are presented in this work. Finally a comparison of the different control methods for instance PI control, MPC, M2PC and DPCVC when used to control the load currents of a direct matrix converter are analysed and included in this thesis.